The Effect of Augmented Reality Shopping Applications on Purchase Intention - Leonnard Leonnard; Annisa S. Paramita; Jasmine J. Maulidiani (Faculty of Economic and Business, 2019)
Augmented reality is a new technological breakthrough that helps e-commerce delivers an online shopping experience with quality of offline shopping. This is possible due to the capability of augmented reality technology that allows consumers to interact and to try products through the virtual world. This technology has not been widely adopted by e-commerce in Indonesia. In this study, we analyzed the effect of this technology on purchase intention through e-consumer experience in the form of perceived enjoyment and usefulness to 89 consumers. Our findings revealed that virtual presence significantly affects the enjoyment and usefulness directly and indirectly to purchase intention. In addition, the device also significantly affects the enjoyment and usefulness directly. Finally, the usefulness is proven to significantly affect purchase intention.